Constitutional and legal foundations of freedom of religion in the Republic of Kazakhstan - Ilyassov, K.T.; Rustembekova, D.K. (Bulletin of the Karaganda University “Law Series”, 2021)
The purpose of the article is to analyze the constitutional legal basis of individual freedom of religion. One of the objectives of the study was to find ways to address the issues of ensuring the rights of the individual, comparing the national legal norms and international legal norms adopted in the Republic of Kazakhstan to ensure freedom of conscience. At the same time, we have proposed norms that ensure social stability by studying the issues of freedom of religion and the protection of national interests. The article discusses in detail the ways to protect human rights on the issue raised using historical, comparative methods of research. In general, religion is a very complex phenomenon and it affects all spheres of society, so when considering the issue of religion, especially when considering the issue of individual religious beliefs, national interests, security issues should not be neglected and adopted norms should take into account this issue. Today is the era of globalization and, accordingly, the growing threat of international religious extremism and terrorism, in which the prevention of dangerous religious movements in the country will remain one of the most pressing issues of national security.